Academic Leadership Development: An Exploratory Study on the Impacts at the Institutional Level Based on an Erasmus+ Capacity Building Project - Ngoc Bich Khuyen Dinh; Chang Zhu; Aysun Caliskan; Zhao Cheng (SAGE Open, 2023)
While demands on academic leadership in higher education have been increasing, there has been a lack of empirical studies exploring the effectiveness and impacts of leadership development interventions. In addition, recent studies suggest a model of leadership development based on an international approach. Unfortunately, the evaluation of those programs is limited in the available literature. This study thus presents the results of the impacts of a higher education (HE) academic leadership development program at the international level which consist of 12 universities in China and Europe. The project was implemented over a 4-year period, delivered through workshops, training programs, and exchanges. Following 2 years of project implementation, the mid-term impact was assessed through surveys and semi-structured interviews. Among the participants who had joined the program for more than 12 months, 51 Chinese participants and 41 European participants voluntarily took part in the online survey; of those, 21 participants were involved in the semi-structured interviews. Ultimately, the findings indicated that the program has had positive impacts on a variety of aspects, including cross-institutional networking, collaboration, partnership, and HE-related policy development and practices. Furthermore, this study has provided empirical evidence on how an academic leadership development program contributes to assisting academic institutions in broadening their connections, networking, and partnerships in order to achieve their institutional goals of development and innovation. As such, the research findings are useful for policymakers, university administrators, and related stakeholders. Lastly, the approaches taken by the academic leadership development program utilized in the current study can be applied widely in different contexts.